Model of asynchronous motor taking into account its magnetic system saturation on basis of Takagi–Sugeno method - N. M. Zaytseva (Омский научный вестник, 2018)
At present asynchronous motors are controlled by means of microprocessors. Modern microprocessor equipment makes it possible to implement any algorithm of electric drive functioning. This is why the paper examines a model of a short-circuited asynchronous motor taking into account nonlinearity of its magnetization parameter. The algorithm implementing saturation of the engine magnetic system is developed with help of TakagiSugeno fuzzy inference. The work describes the suggested membership functions to the intervals of the magnetization vector module and patterns of the functions describing a magnetization curve for each interval. Modeling is done using a MATLAB Simulink system. The paper offers a graphical interpretation of time-superimposed models of a short-circuited asynchronous motor taking into account saturation of asynchronous motor magnetic system realized by means of a sextic polynomial and Takagi-Sugeno fuzzy logic. The algorithms used to describe the saturation are realized using C programming language. The obtained new scientific result can be used in programming microprocessors controlling asynchronous electric drives due to simplicity of its implementation. It is shown that energy-efficient control of modern asynchronous drives must be based on a more adequate model taking into account saturation of the engine magnetic system, which can be done using Takagi-Sugeno fuzzy inference.